Analisis Ekspresif Lirik Lagu “untuk Perempuan yang Sedang Dalam Pelukan” Karya Payung Teduh : Pendekatan Pragmatik - Annisa Dinda Khairani Nasution (BADAN PENERBIT STIEPARI PRESS, 2025)
Song lyrics are often a channel for poets to express a variety of emotions, from love and happiness to sadness and anger. Song lyrics are also an expression of feelings by poets based on their personal experiences. The song lyrics that will be studied in this study are the song